PENGARUH JENIS BIOAKTIVATOR DAN PEMBERIAN BIOCHAR TERHADAP PROSES PENGOMPOSAN SAMPAH ORGANIK - Fabela, Erica; Siswanto, Siswanto; Sasongko, Purnomo Edi (BIOEDUSCIENCE, 2024)
Background: Combining the right bioactivator and biochar dosage can speed up the process and increase the compost quality. Using compost in agriculture can reduce the excessive use of chemical fertilizers, improve soil health and crop yields, and contribute to overall agricultural sustainability. Methods: The research was conducted in March-August 2021 in Kemantren Village, Tulangan District, Sidoarjo Regency. Analysis activities were conducted at the Land Resources Laboratory, Faculty of Agriculture, UPN "Veteran" East Java. This research uses a factorial experimental design based on CRD (Completely Randomized Design) and consists of two factors. Factor 1 is the type of bioactivator, namely: A0: Control; A1: Cattle Farmer; A2: Tapai; and A3: Banana Beetle. Factor 2 provides biochar: B0: Control; B1: 200 grams; and B2: 300 grams. Observation data were analyzed using Analysis Of Variance (ANOVA). Then, if there is a real difference between treatments, the Honest Significant Difference (BNJ) test is carried out with an error rate of 5%. Results: The research results showed that the best compost was the use of a banana hump cultivator, while the best biochar was 200 g. The best results from the combination of bioactivator and biochar were the application of 200 g of cow manure and banana hump bioactivator. Conclusions: The combination of banana stem bioactivators and cow dung with 0 gr biochar (control) improved the quality of the chemical properties of the compost. In contrast, adding biochar at both 200 g and 300 g concentrations showed improvements in the physical quality of the compost texture.